Expanding the therapeutic potential of Salvia miltiorrhiza: a review of its pharmacological applications in musculoskeletal diseases - Ye, Zhiqiang; Liu, Yuyu; Song, Jintong; Gao, Yin; Fang, Haiping; Hu, Zilong; Zhang, Min; Liao, Wenwei; Cui, Liao; Liu, Yanzhi (Frontiers in Pharmacology, 2023)
Salvia miltiorrhiz, commonly known as “Danshen” in Chinese medicine, has longstanding history of application in cardiovascular and cerebrovascular diseases. Renowned for its diverse therapeutic properties, including promoting blood circulation, removing blood stasis, calming the mind, tonifying the blood, and benefiting the “Qi”, recent studies have revealed its significant positive effects on bone metabolism. This potential has garnered attention for its promising role in treating musculoskeletal disorders. Consequently, there is a high anticipation for a comprehensive review of the potential of Salvia miltiorrhiza in the treatment of various musculoskeletal diseases, effectively introducing an established traditional Chinese medicine into a burgeoning field. Aim of the review: Musculoskeletal diseases (MSDs) present significant challenges to healthcare systems worldwide. Previous studies have demonstrated the high efficacy and prospects of Salvia miltiorrhiza and its active ingredients for treatment of MSDs. This review aims to illuminate the newfound applications of Salvia miltiorrhiza and its active ingredients in the treatment of various MSDs, effectively bridging the gap between an established medicine and an emerging field. Methods: In this review, previous studies related to Salvia miltiorrhiza and its active ingredients on the treatment of MSD were collected, the specific active ingredients of Salvia miltiorrhiza were summarized, the effects of Salvia miltiorrhiza and its active ingredients for the treatment of MSDs, as well as their potential molecular mechanisms were reviewed and discussed. Results: Based on previous publications, Salvianolic acid A, salvianolic acid B, tanshinone IIA are the representative active ingredients of Salvia miltiorrhiza. Their application has shown significant beneficial outcomes in osteoporosis, fractures, and arthritis. Salvia miltiorrhiza and its active ingredients protect against MSDs by regulating different signaling pathways, including ROS, Wnt, MAPK, and NF-κB signaling. Conclusion: Salvia miltiorrhiza and its active ingredients demonstrate promising potential for bone diseases and have been explored across a wide variety of MSDs. Further exploration of Salvia miltiorrhiza's pharmacological applications in MSDs holds great promise for advancing therapeutic interventions and improving the lives of patients suffering from these diseases.